VD_FINDINFO Jug / 2013 / 86 vom 4. Dezember 2012 - VD Tribunal cantonal (2012)
ESCROQUERIE, MENACEDROIT PÉNAL, PEINE, SURSIS À L'EXÉCUTION DE LA PEINE, PEINE PÉCUNIAIRE | 146 CP, 180 CP, 19 CP, 34 CP, 41 CP, 44 CP, 47 CP, 97 CP